Pengaruh Komik Digital Terhadap Kemampuan Bahasa Ekspresif Anak di TKIT Wihdatul Ummah Makassar - Nuralia Safitri; Sitti Nurhidayah Ilyas; Fitriani Dzulfadhilah; Usman; Surya; Norma Sulistiyani (STKIP Andi Matappa Pangkep, 2024)
This study aims to find out the impact of the use of digital comic learning media on the development of expressive language of children at Wihdatul Ummah Makassar. The research approach used is a quantitative approach to the type of pre-experimental research. The population in this study is 5-6 years old children at Wihdatul Ummah Makassar TKIT as 52 children. The technique used in the sampling here is Systematic Sampling, a sample in this study consisting of 15 children. Data collection techniques in research are interviews, observations and documentation/archive reports. Verification of validity of findings in research is descriptive statistical analysis and non-parametric statistical analyses. The analysis of data obtained from the pre-test results received an average score of 9.47, whereas from the posttest results a mean score of 17, this suggests that there is a significant change in the development of the expressive language of the child before and after the given digital comic learning media. Based on the Wilcoxom Sign Rank Test obtained Asymp Sig. (2- tailed) 0.001 < 0.05 then it can be concluded there is an influence of the use of digital comic learning media on the development of expressive language of children in Wihdatul Ummah Makassar.